Numerical study of the effect of composition models on cough droplet propagation distributions in confined space. (15th April 2023) - Wang, Tiantian; Shi, Fushan; Shi, Fangcheng; Li, Chunhui; Zhang, Lei; Wang, Jiabin; Jiang, Chen; Qian, Bosen; Dai, Lei; Ji, Peng
Abstract: The compositional models currently used for cough droplet transport and dispersion simulations typically consider water and inorganic salts, ignoring the organics in the droplets. In this study, an organics-ignoring two-composition model and an organics-containing three-composition model of cough droplets are investigated. Computational fluid dynamic (CFD) numerical simulations are conducted to compare the dispersions in the two compositional droplet models under the effect of transient cough jets, and the influences of the compositional model on the transport of cough droplets are revealed. The results show that in the range of 5–50 μm, the two compositional droplet models have essentially the same droplet transport. However, in the range of 50–130 μm, the two models show significant differences in terms of the droplet distribution. The three-composition droplet model has a shorter sedimentation time and fewer suspended droplets than the two-composition model. Therefore, to accurately track the transport process of cough droplets, the organics-containing three-composition droplet model should be used in relevant research. The results of this study provide a scientific basis for accurately predicting the risk of cough droplet propagation and contribute to the development of rational epidemic prevention measures. Highlights: Organic is considered in the cough droplet model, and this composition is ignored by most current numerical studies. The distribution difference between the organics-ignoring and organics-containing droplet models is studied by CFD. Evaporation processes and the number above the mouth of two compositional droplet models are analyzed. Two compositional models smaller than 140 μm can evaporate as droplet nuclei before deposition. The suspension number and settling time of the organics-ignoring model are higher than another (40–130 μm).